986 Feasibility and acceptability of a work-based colorectal cancer screening initiative in florida firefighters. (24th April 2018) - Solle, Natasha Schaefer; Sussman, Daniel; Caban-Martinez, Alberto J; Tse, Colette; Tibangin, Jennifer; Lee, David J; Kobetz, Erin N
Abstract : Introduction: Colorectal cancer (CRC) has been identified as one of the top diagnosed cancers among firefighters in Florida, United States. Firefighters are routinely exposed to highly toxic materials, many of which have been linked to an increased risk for colorectal cancer. Despite the elevated risk, cancer screening behaviours of active firefighters are unknown. We assessed the feasibility, acceptability, and implementation of a worksite-based cancer screening program using faecal immunochemical testing (FIT) among unscreened and under-screened Florida firefighters. Methods: In collaboration with Florida fire departments, participants were recruited through their fire department. All participants completed an eligibility screener, informed consent and demographic questionnaire. Firefighters subsequently received a FIT kit in-person or via mail and returned specimens to the lab for testing. Screening results were reported to participants via telephone and those who screened positive were referred for colonoscopy. Result: Collectively, 1611 firefighters were screened for eligibility of whom 525 (32.6%) were eligible. Ineligible firefighters were mainly excluded due to age (n=635, 58.5%) or were already current with CRC screening recommendations (154 [14.2%] completed FIT in the previous year, and 132 [12.2%] received a colonoscopy in the previous 10 years). FIT kits were sent to 496 of the eligible subjects; 310 (62.5%) participants returned the kits, and 6 (2.0%) received a positive FIT result. All FIT positive participants completed clinical follow-up with colonoscopy screening. Discussion: Firefighters in this study report that using FIT was easy or somewhat easy to perform and would prefer to use this test for screening in the future. Based on these preliminary findings, this workplace screening initiative was both feasible and acceptable in the sample of firefighters. A workplace cancer screening program has potential to increase screening rates in the firefighter population. Additional epidemiologic surveillance for annual screening follow-up is warranted.